Development and Thermal Management of kW-Class High-Power Diode Laser Source Based on the Structure of Two-Stage Combination - Hongbo Zhu; Shengli Fan; Jian Zhao; Xingchen Lin; Li Qin; Yongqiang Ning (IEEE Photonics Journal)
In this paper, we present an optical structure for two-stage beam combination to realize a high-power fiber-coupled diode laser source. In the first stage, dense spectral combination based on reflecting volume Bragg gratings is implemented for combining five diode laser blocks with a spectral separation of 1.5 nm, to a high output power submodule. In the second stage, submodules are further coaxially multiplexed by polarization beam combination and coarse spectral combination to obtain a higher output power. In the process of the beam combination, thermal effects of combining elements are also investigated. By using a temperature control, the diode laser source can steadily produce 3120-W power from an optical fiber with 105-μm core diameter and 0.2 numerical aperture. This paper demonstrates the benefits of this combination structure and the effectiveness of the temperature control.